KESENIAN ISLAM JEMBLUNG DI KABUPATEN KEDIRI - Anwar Dwi Saputra (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: This article examines the Jemblung Islamic art which is popular in Kediri. The focus of the research discussed in this thesis are (1) How did the Jemblung art appear in Kediri (2) What are the elements contained in the Jemblung Islamic Art in Kediri Regency (3) What are the the values ​​contained in Jemblung Islamic Art in Kediri Regency. This study uses cultural methods, namely first data collection, interviews, observation, documentation, data processing, data analysis and the last is interpretation. An anthropological approach is used to explain how to know Jemblung art in Kediri. The theory used by ethnomusicological theory is to analyze the richness of music itself and its function and meaning for society. The researcher concludes that Jemblung is a jarwo dosok which means jenjem-jenjem ewong gemblung (the serene feeling felt by crazy people). This understanding is thought to originate from the tradition of performing Jemblung which places performers of this art like crazy people. Other sources say that the term Jemblung comes from the word gemblung which means crazy. Jemblung in Kediri originates from the myth of Sunan Ngudung who once meditated and had a dream of meditating while accompanied by a tambourine and jidor that read "blung" which became the forerunner of the Jemblung art. Keywords: Islamic art, Jemblung, Kediri